EFEKTIVITAS MEDIA ARTIFICIAL INTELIGENCIA DEEPSEEK DALAM MENINGKATKAN KEMAMPUAN MENULIS TEKS BERITA SISWA KELAS VIII SMP NEGERI 1 CIBALONG - Ayu Puji Rahayu; Erni Fitriani; Dina Agustriani; Budiman Yunus (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to determine the effectiveness of the Artificial Intelligence-based media DeepSeek in improving the news text writing skills of eighth-grade students at SMP Negeri 1 Cibalong. The background of this research lies in students' low writing proficiency, especially in composing structured and linguistically accurate news texts. The study employed a quantitative approach using a pre-experimental design with a one-group pretest-posttest model. The sample consisted of 30 students from a single class. The instruments used were writing tasks and a scoring rubric. Data were analyzed using the Wilcoxon Signed-Rank Test due to the non-normal distribution identified in the normality test. The results showed a significant improvement in students’ writing ability, with an average pretest score of 23.70 and posttest score of 85.20. The Wilcoxon test yielded a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between students' writing skills before and after using DeepSeek. It can be concluded that the DeepSeek media is effective in enhancing students’ news text writing skills, and contributes to the development of Artificial Intelligence-based learning media in Indonesian language education. Keywords: DeepSeek, Artificial Intelligence, writing skills, news text, Indonesian language learning.